The Effect of Financial Literacy on Financial Behavior With Fintech Use as a Moderating Variable - Fadila Jaber; Lalu Hamdani Husnan (PT. Maju Malaqbi Makkarana, 2026)
This research investigates how financial literacy affects the financial behaviors of students on Lombok Island. Utilizing a quantitative methodology, the study surveyed 110 students to gather relevant data. The findings reveal that a higher level of financial literacy has a substantial positive impact on students' financial habits and decision-making processes. Conversely, the role of financial technology (fintech) was found to be substantial in influencing or moderating these behaviors within the studied population. The conclusion emphasizes the importance of enhancing financial literacy programs to foster more responsible and informed financial practices among students. Developing such initiatives can contribute to better financial stability and decision-making skills in the future